A DC Bias Current Reducing Method Considering Grounding Electrode Location and Receiving-end Grid Structure - Lianguang LIU; Chenglian MA (Zhongguo dianli)
Based on the influence of the receiving-end grid structure and the grounding electrode location on DC bias current, this paper analyzes the DC bias current (DCBC) level of the converter station and the adjacent AC substation in the typical connection structure under different connection modes of the AC substations. The factors affecting the DCBC value of converter and AC transformers are analyzed, and the influence mechanism of the grounding electrode location and the receiving-end grid structure on the transformer DCBC value is expounded. Considering the structure of receiving-end grid and the location selection of grounding electrode, a DCBC value reduction method for converter and AC transformers is proposed. The measures to suppress the DC bias current can be analyzed from the aspects of system operation mode selection, grounding electrode location selection, power grid structure planning and designing, etc. This paper proposes to prevent the bias current of the converter and AC transformer during the planning and designing stage.